Revision of the ant genus Mayriella - Shattuck, S. O.; Barnett, N. J. (Memoirs of the American Entomological Institute, 2007)
The ant genus Mayriella is revised at the species level. The genus contains seven species: M. abstinens Forel (north-east Australia and New Zealand), M. ebbei Shattuck & Barnett (new species) (south-east Australia), M. granulata (Vietnam), M. overbecki Viehmeyer (removed from synonymy with M. abstinens) (east-central Australia), M. sharpi Shattuck & Barnett (new species) (eastern Papua New Guinea), M. spinosior Wheeler (north-east Australia) and M. transfuga Baroni Urbani (Nepal and India east to Hong Kong and the Philippines and south to Borneo and Java, Indonesia). M. hackeri Wheeler and M. venustula Wheeler are synonymized with M. abstinens. All species occur in rainforest or wet sclerophyll forests and nest in soil, often under rocks, or in rotten wood on the ground.
Owner: AdminNUSAdded to JabRef: 2013.06.08
Keywords: Formicdae; Mayriella; Myrmicinae